Flipping Listening Comprehension: A Social Media-Integrated Autonomous Learning Framework for EFL Students - Anjarwati, Luluk (Nexus Publishing NXP, 2025)
Listening comprehension remains a critical challenge for EFL students, particularly in fostering autonomous learning. Existing studies highlight that many learners rely heavily on teacher-centered instruction and lack self-regulated strategies to develop independent listening comprehension skills. Although previous research has explored various digital tools, limited attention has been given to the role of social media-based learning platforms, such as the BBC English Course, in supporting self-directed listening development. This study addresses this gap by investigating how a flipped learning approach, integrated with BBC English Course materials, influences EFL students’ autonomous listening comprehension. A sequential mixed-methods design was employed, involving 34 second-semester EFL students at Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, Indonesia. Data were collected through a closed-ended questionnaire measuring self-regulated learning dimensions (goal-setting, self-monitoring, metacognitive strategies, and reflective learning) and structured interviews with six selected students to explore their perceptions and experiences. The findings reveal that exposure to structured, interactive listening activities via social media significantly enhanced students’ ability to regulate their learning, particularly in goal-setting and self-monitoring. However, challenges emerged, including difficulties in identifying relevant learning content and maintaining consistent engagement. Some students expressed frustration with the lack of immediate teacher feedback, which affected their motivation. These findings highlight how the BBC English Course, within social media-integrated flipped learning, uniquely fosters autonomy in listening comprehension. Unlike other digital tools, its structured approach necessitates strategic instructional support. Pedagogical implications stress guided scaffolding and adaptive learning. Future research should examine long-term behavioral shifts and comparative platform effectiveness.